The fictional republic : Horatio Alger and American political discourse - Nackenoff, Carol (OUP E-Books., 1994)
Investigating the enduring quality of Horatio Alger's political theories, this historical study shows how his ideas of hard work tempered by virtue's rewards struck a chord during the economic transformations of the late 19th and early 20th centuries.